A Sociolinguistics Analysis of English Code-Switching in YouTube Podcast - Achwan Sapar; Erni Yuliastri Alpani; Muh Junaidi; Wahyu Kamil Syarifaturrahman (LPPM Universitas Bumigora Mataram, 2023)
This research examined the instances of code-switching based on the theory of Hammers and Blanc (2003) in Deddy Corbuzier's podcast content with Cinta Laura Keihl on his own YouTube channel. It focuses solely on Deddy Corbuzier's utterance. Consequently, there are two goals of this study. The first objective was to determine the type of code-switching, and the second was to determine the frequency of each type to determine which type of code-switching Deddy Corbuzier uses most frequently. Considering the research's data and objectives, the researcher employed the qualitative descriptive method to conduct this research. The data was deemed qualitative because it consisted of written and spoken words as opposed to numbers. And to analyze the data, the writer uses a sociolinguistics approach. Based on the data findings, Deddy Corbuzier performed code-switching at least 79 times in the collected data: 39 times (49.36%) for intra-sentential switching, 36 times (45.56%) for inter-sentential switching, and 4 times (5.06%) for tag-switching. Thus, it can be seen that intra-sentential switching is the type of code-switching that most often appears, which is 39 times, or 49.36%.